2012
DOI: 10.1017/s1751731111001297
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of wheat bran and extruded flax in horses determined from the total collection of feces and acid-insoluble ash as an internal marker

Abstract: Several studies have reported data on comparisons between two methods: the total collection of feces and the internal markers method. The aim of this study was to assess the apparent digestibility of two concentrates and to compare the apparent digestion coefficients using the total collection of feces and acid-insoluble ash (AIA) as the internal marker method. In 2009, six adult geldings aged between 3 and 11 years, with an average weight per trial of 543, 540 and 542 kg, respectively, were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
3
7
1
Order By: Relevance
“…These findings are supported by Takagi et al [21] (intakes were not given) who reported very low (21.8) digestibility for the crude fibre of linseed in horses. In one study, the inclusion of extruded linseed (20% in DM) in the diets of horses decreased the digestibility of nutrients compared to hay-only and hay/wheat bran diets [56]. In agreements with the results of the present study, Smolders et al [57] found increased digestibility values of the diet nutrients when horses were fed compound feed containing (16%) linseed expeller plus more digestible ingredients (cereals).…”
Section: Diet Digestibilitysupporting
confidence: 90%
“…These findings are supported by Takagi et al [21] (intakes were not given) who reported very low (21.8) digestibility for the crude fibre of linseed in horses. In one study, the inclusion of extruded linseed (20% in DM) in the diets of horses decreased the digestibility of nutrients compared to hay-only and hay/wheat bran diets [56]. In agreements with the results of the present study, Smolders et al [57] found increased digestibility values of the diet nutrients when horses were fed compound feed containing (16%) linseed expeller plus more digestible ingredients (cereals).…”
Section: Diet Digestibilitysupporting
confidence: 90%
“…We therefore suggest that lignin cannot be used as a reliable indigestible marker in horses. De Marco et al (2012) have also shown that using AIA as an internal marker led to average values similar to those obtained with total collection. Fecal recovery is reported to be more reliable when the AIA level in feed is increased (McCarthy et al, 1974).…”
Section: Discussionsupporting
confidence: 61%
“…Broken rice has been widely used as a high-energy horse feed in Australia for many years and ground rice hulls have † E-mail: domenico.bergero@unito.it Animal (2014) Determination of apparent digestibility in horses by in vivo trial based on total collection of feces is still considered the best method due to its accuracy (De Marco et al, 2012). Nevertheless, it does have its limits, concerning the direct use of animals, the planning of the experimental procedure and considerable experimentation costs.…”
Section: Introductionmentioning
confidence: 99%
“…Rice-based pellets incorporating rice pollard and broken rice are fed to horses, and the energy values are based on determinations using rice by-products in pig, ruminant and poultry feeds (Farrell and Warren, 1982). McCarthy et al (1989) pointed out that rice milling by-products are high in energy for horses and that broken rice is highly digestible.Broken rice has been widely used as a high-energy horse feed in Australia for many years and ground rice hulls have † E-mail: domenico.bergero@unito.it Animal (2014) Determination of apparent digestibility in horses by in vivo trial based on total collection of feces is still considered the best method due to its accuracy (De Marco et al, 2012). Nevertheless, it does have its limits, concerning the direct use of animals, the planning of the experimental procedure and considerable experimentation costs.…”
mentioning
confidence: 99%